1992
DOI: 10.1103/physrevc.45.r1424
|View full text |Cite
|
Sign up to set email alerts
|

S-matrix poles and phase shifts forNΔ scattering

Abstract: Threshold behavior of S-wave phase shifts is studied for Nh, scattering with a nearby S-matrix pole. The phase 8n& for pp ('D~) Nh ('S~) obtained by experiments for pp nptt+ are explained on the basis of the pole of unstable bound state type or broad dibaryop, (M =2144 MeV, I = 1, J =2+), by taking into account instability of the 6, NN final-state interaction for Nh, npn+ and a factor i due to p-wave pion emission. This pole explains also the '02 phase parameters for pp pp around 2144 MeV in Es. PACS number(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 17 publications
9
21
0
Order By: Relevance
“…Refs. [61][62][63][64][65][66][67][68][69][70][71][72]. Since in this route D 12 and the associated pion have to be in relative p-wave, in order to fulfill the angular momentum requirements of D 03 , this decay route is practically indistinguishable from the route D 03 → ∆∆ → dππ, i.e.…”
Section: ∆∆ Final State Interactionmentioning
confidence: 99%
“…Refs. [61][62][63][64][65][66][67][68][69][70][71][72]. Since in this route D 12 and the associated pion have to be in relative p-wave, in order to fulfill the angular momentum requirements of D 03 , this decay route is practically indistinguishable from the route D 03 → ∆∆ → dππ, i.e.…”
Section: ∆∆ Final State Interactionmentioning
confidence: 99%
“…In a series of papers [38,39] Hoshizaki concluded that interpretations in terms of a NΔ virtual-state pole or a threshold cusp are invalid, rather it constitutes a S -matrix pole at (2144 -i55) MeV. But still we are left with the problem that these values do not deviate significantly from what is expected for a conventional Δ excitation by t-channel meson exchange between the two nucleons.…”
Section: A Remnant From This Period -A Resonance In Thementioning
confidence: 93%
“…The D 12 dibaryon of Table 1 shows up clearly in the Argand diagram of the NN 1 D 2 partial wave which is coupled above the NNπ threshold to the I = 1 s-wave NΔ channel. Its S -matrix pole position W = M − iΓ/2 was given by 2148−i63 MeV in NN phase shift analyses [7] and by 2144−i55 MeV in dedicated pp ↔ npπ + coupled-channels analyses [8]. Values of D 12 and D 21 pole positions from our hadronic-model three-body πNN Faddeev calculations [5,6] described in the previous subsection are listed in Table 2.…”
Section: Pion Assisted Nδ and δδ Dibaryonsmentioning
confidence: 99%